Minimal dynamical system with given D-function and topological entropy - Ye, Xiang dong (Ukrains’kyi Matematychnyi Zhurnal, 1993)
The D-function is a new topological invariant introduced by the author in [3] to classify the minimal dynamical system and to generalize Sharkovskii’s theorem on the coexistence of periodic orbits. We show that the D-function and the topological entropy are independent.